Complex Pitch Perception Deficits in Dyslexia Persist Regardless of Previous Musical Experiences. - Kelemen, Delaney E.; Burnsworth, Camden; Chubb, Charles; Centanni, Tracy M. (Journal of Speech, Language & Hearing Research, 2025)
Purpose: Pitch perception is important for speech sound learning, and reading acquisition requires integration of speech sounds and written letters. Many individuals with dyslexia exhibit auditory perception deficits that may therefore contribute to their reading impairment given that complex pitch perception is crucial for categorizing speech sounds. Given rising interest in music training as a reading intervention, understanding associations between prior music experiences and pitch perception is important. This study explored the relationship between pitch perception skills and reading ability in young adults with and without dyslexia with various levels of musical experience. Method: Young adults (18--35 years old) with (N = 43) and without (N = 105) dyslexia completed two pitch perception tasks, reading assessments, and a survey reporting formal music training and childhood home music environment (HME). Results: Participants with dyslexia performed worse than typically developing peers on both pitch perception tasks. Single-word reading was related to pitch perception in the typically developing group only. Childhood HME positively correlated with mode categorization and simple pitch discrimination in both groups. Formal music training was associated with performance on both pitch perception tasks in the typically developing group, and simple pitch discrimination in the dyslexia group. Conclusions: Pitch perception deficits may interfere with complex acoustic categorization and persist in some individuals with dyslexia despite prior music experiences. Future research should investigate the link between pitch perception and phonological awareness in dyslexia and assess whether music interventions targeting these skills improve reading.